2021
DOI: 10.1101/2021.01.15.426786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omic rejuvenation of human cells by maturation phase transient reprogramming

Abstract: Ageing is the gradual decline in organismal fitness that occurs over time leading to tissue dysfunction and disease. At the cellular level, ageing is associated with reduced function, altered gene expression and a perturbed epigenome. Somatic cell reprogramming, the process of converting somatic cells to induced pluripotent stem cells (iPSCs), can reverse these age-associated changes. However, during iPSC reprogramming somatic cell identity is lost, and can be difficult to reacquire as re-differentiated iPSCs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…Another important question was whether the partially reprogrammed cells would retain their lower eAge and show a stable rejuvenated phenotype after reversion to somatic state, or would they quickly revert back to their original eAge? A recent preprint by Gill et al addressed these questions using a similar in vitro reprogramming system with fibroblasts from middle aged donors and discontinuing OSKM expression after days 10, 13, 15 or 17 [73]. Importantly, the study confirmed a rejuvenated phenotype of the transiently reprogrammed cells, which is maintained upon reversion to somatic state at least four weeks after OSKM withdrawal.…”
Section: Reprogramming-induced Epigenetic Rejuvenationmentioning
confidence: 94%
See 2 more Smart Citations
“…Another important question was whether the partially reprogrammed cells would retain their lower eAge and show a stable rejuvenated phenotype after reversion to somatic state, or would they quickly revert back to their original eAge? A recent preprint by Gill et al addressed these questions using a similar in vitro reprogramming system with fibroblasts from middle aged donors and discontinuing OSKM expression after days 10, 13, 15 or 17 [73]. Importantly, the study confirmed a rejuvenated phenotype of the transiently reprogrammed cells, which is maintained upon reversion to somatic state at least four weeks after OSKM withdrawal.…”
Section: Reprogramming-induced Epigenetic Rejuvenationmentioning
confidence: 94%
“…B OSKM treatment increased lifespan of progeria mice, improved the regenerative capacity of muscle and pancreas, as well as glucose tolerance [74]. C Overlaid summary of iPSC reprogramming time-course experiments by [118] and [73]. Upper panel: Horvath multi-tissue age predictor applied to OSKM-expressing adult fibroblasts [118] partially dedifferentiating and producing a rejuvenative effect to surrounding cells by being more stem-like?…”
Section: Reprogramming-induced Epigenetic Rejuvenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have suggested that epigenetic mechanisms may play a role in controlling lifespan and aging [7][8][9][10][11][12][13][14][15] . The role of epigenetics in mammalian aging is underscored by recent studies demonstrating age reversal through (transient) epigenetic reprogramming with Yamanaka factors [16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…It is made The copyright holder for this preprint this version posted March 12, 2021. ; https://doi.org/10.1101/2021.03.11.435028 doi: bioRxiv preprint and growth hormone receptor knockout (30)(31)(32)(33)(34)(35)(36). Most importantly, the clocks developed based on aging patterns of mostly adult tissues report the effects of cell rejuvenation upon complete-or partial reprogramming of adult fibroblasts into induced pluripotent stem cells (iPSCs) as demonstrated in both human and mouse (33,35,(37)(38)(39). Even though iPSCs correspond to an embryonic state and the transition to these cells involves major molecular changes, including changes in the epigenome, this rejuvenation event can be assessed by epigenetic clocks.…”
mentioning
confidence: 99%